Traditional Knowledge Management and Usage of Medicinal Plants as Daily Medication in Healing Rituals Among the Batek of Kuala Koh, Gua Musang, Kelantan :an Exploratory Evidence - Alias, Amran; Salleh, Hood; Mohamad Ismail, Shaharuddin; Aziz Abdul Ghani Aziz, Sarah; Suhaidi Salleh, Mohd; Anuar Kamri, Khairol; Noor Saarani, Asmawi; Daud Druis, Mohamad (International Journal of Engineering and Technology, 2018)
Traditional knowledge related to medicinal plants of the indigenous people are indeed a useful asset for the community. The knowledge that had been traditionally inherited from their ancestors is an integral part of their survival as they live symbiotically with the forests. While many researches and literatures are focusing on documenting and recording these knowledge, not much has been researched in understanding the holistic process of the knowledge management particularly at the indigenous community level. This paper provides an attempt to reveal empirical findings about the management and use of medicinal plants in ailment healing rituals. In order to enable a holistic view of the management of knowledge at the study site, the main question asked was what happened during the four processes of knowledge management namely knowledge generation, knowledge codification, knowledge utilization and knowledge transfer. Using the Batek community of Kuala Koh, Gua Musang, in the state of Kelantan as a case study, ethnographic methods of individual and group interviews, observations and participants observations as well as document analysis, were employed to gather the data from the study site and the grounded theory approach was used for data analysis to enable the emergence of the themes to understand the phenomena at the study site. The study, conducted from 2014-2016, involved prolonged stays with the community. The findings revealed that there was an â€˜undocumented means of knowledge generation with potential loss of traditional knowledgeâ€™, while there was a non-codified knowledge being practiced in the community and widespread inability of basic reading and writing skills among younger generation. In addition, there was a high level of traditional knowledge utilisation in the community but some procedures such as ritual practices have been simplified while there was a complete absence of documentation of traditional knowledge by members of the community that might weaken knowledge transfer.Â